Opinions on the Internet of Things in the Industrial Design Curriculum - Page, Tom (Design and Technology Education: An International Journal, 2016)
The aim of this work investigated whether there is a need to incorporate the Internet of Things (IoT) into the Industrial Design curriculum. Initial research comprised a literature review into the origins, growth, challenges and enabling technologies for the IoT. Furthermore, literature around IoT within the current curriculum and for industrial designers and graduates was explored. Whilst this work considers the possibilities and capabilities through various visions and methods of application, the fundamentals of the technical side are considered in order to understand these possibilities for the IoT as a subject. A mixed-method approach was designed which used a structured questionnaire survey for industrial design students and interviews with design lecturers. The results revealed a majority agreement into the need and interest for Industrial Design Curriculum to incorporate IoT subject matter, however, with much debate and discussion into how this may be envisioned. The work concludes with implementation through a mixed approach to teaching microcontroller design applications combined with projectled problem based learning allowing students to combine their design skills into product concepts and prototypes in order to realise and develop the future Internet of Things.